Ground state cooling in a hybrid optomechanical system with a three-level atomic ensemble. (24th January 2018) - Li, Tan; Zhang, Shuo; Huang, He-Liang; Li, Feng-Guang; Fu, Xiang-Qun; Wang, Xiang; Bao, Wan-Su
Abstract: Cooling mechanical resonators are of great importance in both fundamental study and applied science. We investigate the hybrid optomechanical cooling with a three-level atomic ensemble fixed in a strong excited optical cavity. By using the quantum noise approach, we find the upper bound of the noise spectrum and further present three optimal parameter conditions, which can yield a small heating coefficient, a large cooling coefficient, and thus a small final phonon number. Moreover, through the covariance matrix approach, results of numerical simulation are obtained, which are consistent with the theoretical expectations. It is demonstrated that our scheme can achieve ground state cooling in the highly unresolved sideband regime, within the current experimental technologies. Compared with the previous cooling methods, in our scheme, there are fewer constraints on the drive strength of atomic ensemble and number of atoms in the ensemble. In addition, the tolerable ranges of parameters for ground state cooling are extended. As a result, our scheme is very suitable for experiments and can be a guideline for the research of hybrid optomechanical cooling.